A study of fetomaternal outcome in pregnancy beyond expected date of delivery in obstetrics and gynaecology department of a tertiary health care center of South Gujarat - Pipaliya, Jay B.; Bhatia, Saral G.; Udhnawala, Parul (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Post-dated pregnancy is that extends beyond 40 weeks plus one or more days (anytime past the estimated due date). Mother and the foetus are at increased risk of adverse events when the pregnancy continues beyond the expected date of delivery (EDD). Method: This prospective observational study was conducted at obstetrics and gynaecology department of tertiary care centre of South Gujarat for 1 year period after official approval from human research ethical committee. Results: In our study total 200 postdated pregnant women included. Majority i.e. 134 (67%) patients had delivered as normal vaginally, whereas 68 (34%) patients required caesarean section. The most common indication for cesarean section was meconium-stained liquor (42.6%, n=68) follow by fetal distress, 2nd stage CPD, non-progress of labor, failure of induction etc. Altogether 19 newborn need NICU admission for different complication of which the most common neonate’s complication was perinatal asphyxia followed by meconium aspiration syndrome and RDS and only one neonate had early neonate death (END) due to RDS. Conclusions: In pregnancies beyond 40 weeks, timely confirmed of postdated pregnancy, effective fetal monitoring and timely induction and with proper intervention could preclude the adverse feto-maternal outcome.